A sensitive biomimetic enzyme-linked immunoassay method based on Au@Pt@Au composite nanozyme label and molecularly imprinted biomimetic antibody for histamine detection. Issue 1 (1st January 2021) - Wang, Xiaofeng; Chen, Yongfeng; Yu, Runze; Wang, Ruiqiang; Xu, Zhixiang
ABSTRACT: In this paper, a sensitive biomimetic enzyme-linked immunoassay (BELISA) method based on an Au@Pt@Au composite nanozyme label was developed for histamine (HA) detection. A molecular imprinted polymer prepared directly on the 96-well plate served as a biomimetic antibody. A BELISA method was developed for HA standard solutions at concentrations ranging from 0.01 to 100.00 mg/L. Under optimal conditions, the novel BELISA method had a low limit of detection (0.069 mg/L) and high sensitivity (7.20 mg/L). The HA spiked in yellow rice wine and liqueur samples were detected by this BELISA method with the recoveries ranging from 84.28% to 108.82%. There was no significant difference of the results between the BELISA method and HPLC for the detection of HA in the red and white grape wine samples.